REFERENCE GRAPHIC SCHEMES IN THE SYSTEM OF LESSONS ON RUSSIAN LITERATURE (World Bulletin of Social Sciences, 2023)
The article is devoted to the communicative-activity approach to the study of Russian literature by schoolchildren for whom Russian is not their native language. The article presents the experience of designing lessons for the study of the tale of A. Pushkin. The examples of achieving performance in terms of skills and competencies, the implementation of integrated teaching of speech activity, a combination of types of educational activities are shown. The experience of didactics is generalized from the standpoint of motivation to study a second language and literature, and the formation of effective communication skills.